Coinstantaneous removal of nitrate and phenol by modified corncob and manganese dioxide based immobilized bioreactor: Enhancement and microbial synergistic mechanisms. Issue 2 (April 2023) - Zeng, Yuxin; Ali, Amjad; Su, Junfeng; Zhai, Zhenyu; Huang, Tinglin; Gao, Zhihong
Abstract: In this study, polyvinyl alcohol (PVA), modified corncob powder and manganese dioxide (PCCM) cubes were prepared for entrapping Cupriavidus sp. ZY7 and Pantoea sp. MFG10 in the bioreactor. The denitrification and phenol removal efficiencies reached 89.38% and 89.17% at carbon to nitrogen (C/N) ratio of 1.0, hydraulic retention time (HRT) of 6 h, and the nitrate and phenol concentration of inflow was 15 and 1 mg L −1, respectively. Strain ZY7 could degrade cellulose in corncob to provide available carbon source in the bioreactor, and the enhancement effect was more obvious as C/N ratio increased. High-throughput data confirmed that Cupriavidus and Pantoea were the prevalent strains in the PCCM cubes bioreactor. The synergistic relationship between strains ZY7 and MFG10 was the key to the excellent pollutants removal ability of the bioreactor at low C/N ratio, which was important for the treatment of wastewater with complex contaminants. Graphical Abstract: ga1 Highlights: An immobilized biocarrier combining corncob and manganese dioxide was developed. The bioreactor removed nitrate and phenol effectively under low C/N ratio. Strain ZY7 promoted cellulose degradation to provide an available carbon source. Synergistic relationship between microorganisms played a vital role in bioreactor. Cupriavidus and Pantoea proved to be the main contributors to the bioreactor.